Searching for peace in Asia Pacific : (Lynne Rienner, 2004)
Third in an acclaimed series, Searching for Peace in Asia Pacific offers critical background information, up-to-date surveys of the conflicts in Northeast Asia, Southeast Asia, and the Pacific, and a directory of some 400 organizations working in the field of conflict prevention and peace-building in the Asia Pacific region. The authors provide detailed, objective descriptions of ongoing activities, as well as assessments of the prospects for conflict resolution.